Analisis Kebutuhan Bahasa Inggris Pariwisata pada Siswa SMA di Thailand: Studi Survei Mata Pelajaran English for Tourism - Lailiy Kurnia Ilahi; Wahyudi Wahyudi; Novinda Rosayanti; Miftahul Mahrus; Budyi Suswanto (Penerbit Widina, Widina Media Utama, 2025)
This study aimed to analyze the needs of English language use for tourism among senior high school students in Thailand who take the English for Tourism subject. The research focused on identifying the most required language skills, the skills that are the most difficult to master, and students’ perceptions of English learning in the tourism context. A descriptive survey design was employed, involving 120 students selected through quota sampling and proportionally distributed based on grade level. The research instruments consisted of a students’ perception questionnaire and semi-structured interviews. The questionnaire data were analyzed using descriptive statistics, namely mean and standard deviation, while the interview data were analyzed through content analysis. The findings revealed that speaking and listening were the most needed as well as the most problematic skills in learning English for Tourism. Limited vocabulary, insufficient grammatical competence, and low self-confidence were identified as the main factors hindering students’ oral communication ability. In addition, the students demonstrated positive attitudes toward the English for Tourism subject and perceived it as relevant for supporting their academic readiness and future career opportunities in the tourism sector. This study emphasizes the importance of developing English for Tourism instruction based on students’ needs analysis, with a strong focus on strengthening oral communication skills, integrating authentic materials, and implementing contextual and communicative learning strategies.ABSTRAKPenelitian ini bertujuan untuk menganalisis kebutuhan penggunaan bahasa Inggris untuk pariwisata pada siswa SMA di Thailand yang mengikuti mata pelajaran English for Tourism. Penelitian difokuskan pada identifikasi keterampilan bahasa yang paling dibutuhkan, keterampilan yang paling sulit dikuasai, serta persepsi siswa terhadap pembelajaran bahasa Inggris dalam konteks pariwisata. Metode yang digunakan adalah survei deskriptif dengan melibatkan 120 siswa sebagai responden yang dipilih melalui teknik quota sampling dan didistribusikan secara proporsional berdasarkan tingkat kelas. Instrumen penelitian berupa kuesioner persepsi siswa dan wawancara semi-terstruktur. Data kuesioner dianalisis menggunakan statistik deskriptif berupa nilai rata-rata dan standar deviasi, sedangkan data wawancara dianalisis menggunakan analisis isi. Hasil penelitian menunjukkan bahwa keterampilan berbicara (speaking) dan menyimak (listening) merupakan keterampilan yang paling dibutuhkan sekaligus paling bermasalah dalam pembelajaran English for Tourism. Keterbatasan kosakata, penguasaan tata bahasa, serta rendahnya kepercayaan diri menjadi faktor utama yang menghambat kemampuan komunikasi lisan siswa. Selain itu, siswa menunjukkan sikap positif terhadap mata pelajaran English for Tourism dan menganggapnya relevan untuk mendukung kesiapan akademik dan peluang karier di sektor pariwisata. Penelitian ini menegaskan pentingnya pengembangan pembelajaran English for Tourism yang berbasis analisis kebutuhan siswa, dengan penekanan pada penguatan keterampilan komunikasi lisan, penggunaan materi autentik, serta penerapan strategi pembelajaran komunikatif yang kontekstual dan aplikatif.